Quick Insight into the Indian Railways Passengers’ Perception on the SERVICE QUALITY – with respect to the Delhi Division - Choudhary, Atul; Bansal, Sanjeev; Sharma, Prashant; Prashaant, Anu (International Journal of Engineering and Technology, 2018)
India with the Worldâ€™s second largest population that certainly contributes of an increase of passengersâ€™ travelling demands. IR gives the option of cheap as well as comfortable trains for our transportation. However, with growing awareness, passengers look for a better quality of services. This paper refers to the important dimensions which can make a difference in the passengersâ€™ service quality in the Delhi Division of Northern Railways.Â Â